PENGARUH DAU & DAK TERHADAP PERTUMBUHAN EKONOMI KOTA BANJARMASIN - MUHAMMAD FAJRUL AHADDIN; MUHAMMAD SALEH (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The Influence of General Allocation Funds and Special Allocation Funds to Economic Growth in Banjarmasin City. Economic growth or economic growth is the aggregate increase in national income or increase in output within a certain time.The population in this study is the Government of Banjarmasin City of South Kalimantan Province. Hypothesis testing in this study using multiple linear regression. The have been collected is data analyzed first with classical assumption test then hypothesis tested by SPSS 20 test instrument. The results showed that the General Allocation Fund had a positive effect on economic growth. It was evident from the results of the t test obtained a significant value of 0.028 <α where (α = 0.05) and Special Allocation Funds the t test results were 0.002 <α where (α = 0.05). The most dominant variable influencing economic growth in Banjarmasin City is the Special Allocation Fund because it has the smallest probability.Keyword: General Allocation Funds, Special Allocation Funds dan Economic Growt.